Incidental Detection of Onchocerca Microfilariae in Donkeys (Equus asinus) in Italy: Report of Four Cases - Papini, Roberto Amerigo; Lubas, George; Sgorbini, Micaela (Frontiers in Veterinary Science, 2020)
The occurrence of autochthonous Onchocerca infection in donkeys is reported for the first time in Italy. Four jennies, bred on the same farm, were referred to the Veterinary Teaching Hospital for reproduction assistance and artificial insemination (n=3) or for veterinary support during the delivery (n=1). Microfilariae were incidentally detected during the blood smear examination of one jenny. Then, peripheral blood samples were collected from the other three jennies and the presence of microfilariae was investigated by the Knott’s test. Circulating unsheathed microfilariae were identified in all the animals. The level of microfilaraemia was between 1 and 31 microfilariae in 2 mL of blood. Hematological changes showed moderate eosinophilia in one case or both remarkable eosinophilia and basophilia in another case. Based on molecular findings by PCR and sequencing, the microfilariae showed 98% sequence similarity with Onchocerca sp in the NCBI GenBank database (Accession no.: MK541848.1). The present report provides evidence that Onchocerca is an etiological agent of parasitic infection in donkeys in Italy. Our findings highlight the importance of screening in donkeys for Onchocerca even in the absence of clinical indications.